Zofia Szczupaczyńska wobec wyzwań swoich czasów. Uwagi na marginesie lektury cyklu „krakowskich kryminałów” Maryli Szymiczkowej [właśc. Jacek Dehnel i Piotr Tarczyński] - Adam Mazurkiewicz (Literatura i Kultura Popularna)
The ‘Kraków series’ of detective stories by Maryla Szymiczkowa has been interpreted in various contexts. Among them, there were also considerations that situated the tetralogy against the backdrop of contemporary transformations of the ‘crime and punishment’ story (whether the cycle itself can be considered as representative to crime fiction is a separate issue). Most often, however, the stories about the adventures of the protagonist of the series, Zofia Szczupaczyńska, are situated in the context of nostalgic literature and games taken up by Szymiczkowa. Those in turn lead to the demythologization of the image of Kraków’s ‘Galician-ness’ at the turn of the 19th and 20th centuries, well established in Polish culture, along with the perception of social relations characteristic of that period. The tension that arises between artistic creation and historically attested information makes us look at the protagonist of the story as a person functioning in two mutually complementary — but also conflicting — social and moral realities. As a ‘citizen of two worlds,’ Szczupaczyńska remains torn between bourgeois traditionalism and the challenges of the new age.